Evaluation of Size-Specific Dose Estimates (SSDE) in paediatric body imaging using 320-detector CT - Admontree, Saifhon; Junsorn, Sawitree; Tathip, Rattanaporn; Todsatidpaisan, Supannika; Buachan, Pranee; Asavaphatiboon, Sawwanee (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 2 (2019): April-June 2019, 2019)
The radiation dose from CT is considered a high risk measure in diagnostic radiology. The American Association of Physicists in Medicine (AAPM) Report No. 204 has concerned the CT dose which depends on the patient size especially in the paediatric patients. We therefore used the conversion factor in AAPM 204 to evaluate size-specific dose estimates (SSDE) of the volumetric computed tomography dose index (CTDI vol ) for paediatric body CT imaging with 320 slice CT which is used for routinely in paediatric cases at Ramathibodi Hospital. Purpose of the study was to evaluate and compare SSDEs to displayed CT scanner output in paediatric chest and abdomen examinations acquired on 320-detector CT. Quality control was performed prior to data collection. A retrospective analysis categorized 525 paediatric CT examinations (224 chest, 92 abdomen, and 209 chest including abdomen) into four age groups. SSDE conversion factors were used as a function of effective diameter for 32-cm-diameter PMMA phantom to estimate the patient dose, based on scanner output index (displayed CTDI vol ) and patient sizes. Results showed that the highest percentage difference between the displayed and SSDE CTDI vol was found in the youngest age group (0-<1 year old). In conclusion, we found that size-specific dose estimation for CT results in dose estimates different to those displayed on the CT scanner, especially in a small-sized paediatric population. The percentage differences of size-specific dose estimation CTDI vol values from displayed values in each age group for chest, abdomen and chest including abdomen CT were 133/117/85/103, 124/100/83/65 and 112/105/91/68, respectively. Radiologists should be concerned about these differences, and diagnostic technologists should estimate the SSDE dose and adjust scanning parameters appropriately before performing the CT scan. To ensure that radiation dose does not exceed diagnostic reference levels. Keywords : 320-detector CT, size-specific dose estimates (SSDE), volume computed tomography dose index (CTDI vol ), paediatric CT, diagnostic reference levels (DRLs).